2022
DOI: 10.3390/jof8101099
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Contamination in Microalgal Cultivation: Biological and Biotechnological Aspects of Fungi-Microalgae Interaction

Abstract: In the last few decades, the increasing interest in microalgae as sources of new biomolecules and environmental remediators stimulated scientists’ investigations and industrial applications. Nowadays, microalgae are exploited in different fields such as cosmeceuticals, nutraceuticals and as human and animal food supplements. Microalgae can be grown using various cultivation systems depending on their final application. One of the main problems in microalgae cultivations is the possible presence of biological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“…However, to be considered for harvesting, the fungi should not be environmentally harmful and safe for downstream applications, such as feeds (Ummalyma et al, 2017). Interestingly, the co-existence of fungi with microalgae protects cultures from external microbial contaminations (Laezza et al, 2022). Similarly, it was reported that the presence of fungi in microalgae biomass did not change its bio-oil or carbon, hydrogen, or nitrogen contents and overall biomass composition (Li et al, 2017).…”
Section: Co-cultivation Of Microalgae and Fungimentioning
confidence: 99%
“…However, to be considered for harvesting, the fungi should not be environmentally harmful and safe for downstream applications, such as feeds (Ummalyma et al, 2017). Interestingly, the co-existence of fungi with microalgae protects cultures from external microbial contaminations (Laezza et al, 2022). Similarly, it was reported that the presence of fungi in microalgae biomass did not change its bio-oil or carbon, hydrogen, or nitrogen contents and overall biomass composition (Li et al, 2017).…”
Section: Co-cultivation Of Microalgae and Fungimentioning
confidence: 99%
“…Microalgae cultures can be affected by, inter alia, several species of fungi, some of which have not yet been fully identified 16 , 17 . Fungi usually grow at temperatures between 0 and 30 °C, but there are various species that can grow at temperatures close to 50 °C, or below 10 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the presence of organic substrates facilitates the proliferation of microbial communities (e.g., fungi, bacteria, viruses, and others) in the medium because these microbes generally grow faster than microalgae 15 . For some specific algae production purposes such as pharmaceuticals, cosmetics or food, the algal biomass cannot be contaminated.Microalgae cultures can be affected by, inter alia, several species of fungi, some of which have not yet been fully identified 16,17 . Fungi usually grow at temperatures between 0 and 30 °C, but there are various species that can grow at temperatures close to 50 °C, or below 10 °C.…”
mentioning
confidence: 99%